TRANSLATORS AS CULTURAL MEDIATORS (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article argues that memoir translators do far more than substitute words; they act as cultural mediators whose personal lifeworlds shape every semantic choice. Drawing on phenomenology, affect theory and recent Uzbek-language scholarship, it shows how translators’ memories, value frameworks and emotional repertoires guide the reframing of culturally charged episodes, the management of silence and even the pacing of narrative time. A critical synthesis of interview-based studies and textual comparisons reveals patterns of “selective resonance,” whereby translators foreground experiences that echo their own while damping discordant images. Pedagogical and ethical implications are outlined for training programmes in global and Uzbek contexts.